Handle with care: challenges associated with ultra-processed foods research - O'Connor, LE; Herrick, KA; Papier, K (Oxford University Press, 2024)
The World Health Organization and a number of countries have long recommended increasing the consumption of fibre, fruit and vegetables, and limiting intakes of foods that are energy dense and high in saturated fat, free sugars and salt, for disease prevention. More recently, there has been debate about whether dietary guidance about ultra-processed foods (UPFs) is needed. Ultra-processed foods are defined as ‘industrially manufactured products made up of several ingredients (formulations) including sugar, oils, fat, and salt (generally in combination and in higher amounts than in processed foods) and food substances of no or rare culinary use’.1 High intake of UPFs is associated with a higher risk of several poor health outcomes in observational epidemiological analyses2 and with excess energy intake and weight gain in one randomised controlled trial.3 Beyond the nutrient composition there are additional proposed mechanisms that suggest negative health outcomes from consuming high amounts of these products.4 For example, mechanisms that affect food choice (including e.g. cost, shelf-life, packaging, hyper-palatability and hunger stimulation/fullness suppression), mechanisms that may lead to over-consumption (e.g. including digestive processes that have yet to be described, by altering oral processing effort, eating rate, gastric emptying time, gastrointestinal transit time and perturbations in the microbiome), and mechanisms relating high consumption with disease outcomes (e.g. excess energy intake and weight gain). However, data on many of these proposed mechanisms are not supportive of these hypotheses or are lacking.4 There could be yet unknown pathways to consider as well. Aside from mechanisms, questions remain about whether classifying foods based on processing contributes additional value beyond conventional dietary recommendations.5 Further, there are noted concerns about the definition, validity and reproducibility of food processing classification systems.6,7 This presents challenges for interpreting associations with health outcomes observed in the literature.